Aspidistra magnifica (Asparagaceae), a new species from Central Vietnam - Lý, Ngọc-Sâm; Nguyen, Khang Sinh; Hoàng, Thanh-Sơn; Đỗ, Văn-Nhân; Tillich, Hans-Juergen (Phytotaxa, 2021)
Aspidistra magnifica, a new species from Mount Cà Đam, Quảng Ngãi Province, Central Vietnam, is described and illustrated. It is similar to A. maguanensis in having purple-black flowers, twelve perigone lobes and stamens, and a table-shaped pistil, but differs by its somewhat elliptic leaf blades, short flowering peduncles, much large broadly campanulate to bowl shaped perigone tube, longer outcurved perigone lobes and larger rounded stigma. A morphological description, two colour plates, the distribution, ecological information, the conservation status, and a comparison table of similar species are given.